A ball-milling synthesis of N-graphyne with controllable nitrogen doping sites for efficient electrocatalytic oxygen evolution and supercapacitors. Issue 31 (29th July 2020) - Ding, Wen; Sun, Mingxuan; Gao, Bowen; Liu, Wenzhu; Ding, Zhipeng; Anandan, Sambandam
Abstract : N-Graphyne, with a novel structure, was synthesized by the one-step ball milling of CaC2 and pyrazine; its excellent electrocatalytic and supercapacitor properties were confirmed. Abstract : Low-cost and efficient multifunctional electrodes play an important part in promoting the practical application of energy conversion and storage. Herein, we report the facile synthesis of N-graphyne, with a novel structure, by one-step ball milling of CaC2 and pyrazine. The accurate doping of nitrogen atoms at the controllable sites of the molecular skeleton of γ-graphyne was achieved using the nitrogenous precursor (pyrazine) as a reactant. Various techniques were adopted for the investigation of the composition, structure, and morphology of the obtained samples. The electrochemical measurements demonstrated that N-graphyne can serve as an excellent electrode material for both electrocatalysis and supercapacitors. As an electrocatalyst, N-graphyne exhibited an overpotential of 280 mV at 100 mA cm −2 and a Tafel slope of 122 mV dec −1 for the oxygen evolution reaction with highly stable morphology and electrocatalytic performance. As a supercapacitor electrode, N-graphyne showed a maximum capacitance of 235 F g −1 at 1 A g −1, and capacitance retention of 87% after 3000 cycles. The superior electrochemical performance of N-graphyne is due to the nitrogen heteroatomic defects, large electrochemical active surface areas and fast electron migration. Our studies provide a facile synthesis of novel N-graphyne with controllable doping sites and promote its potential applications in electrocatalysis and supercapacitors.